Классификация не-предикатно-структурированных высказываний по коммуникативному типу предложения - Образцова, Ольга В’ячеславівна; Obraztsova, O. V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Стаття присвячена висловленням, які не представляють собою структуру предикації в її повному та експліцитному вигляді, умовно названими «не-предикатно-структурованими висловленнями (НПСВ)». У статті подано короткий огляд точок зору на визначення синтаксичного статусу таких речень; запропоновано принципи та критерії класифікування не-предикатно-структурованих висловлень. На основі проведеного дослідження, опису і кількісних показників функціонування таких висловлень у сучасній англомовній художній прозі представлено результати класифікування НПСВ відповідно до комунікативного типу речення. Зокрема, виявлено тенденцію до поширення вживання НПСВ у сучасному художньому тексті, значну частотність НПСВ спонукально-окличного комунікативного типу. The article is devoted to sentences which do not present a complete explicit structure of predication. Their syntactic status is determined contradictorily, as it is seen from the brief theoretical review presented in the article, so the author defines such sentences as «non-predication-structured utterances (NSPU)». In order to ascertain their syntactic status some principles and criteria for classifying them are offered. One such typology (that of communicative sentence types) is presented based upon the results of NPSU usage in modern (published within years 2000–2010) English and American fiction. Non-predication-structured utterances are found to be increasingly frequent in modern English prose, as well as rather frequent are NSPU-Imperative-Exclamatory sentences.
On Classifying Non-predication-structured Utterances According to the Sentence Communicative Type
Keywords: не-предикатно-структурированное высказывание; non-predication structured utterance; структура предикации; structure of predication; эллипсис; ellipsis